Reflection on English Textbook in the Kenyan classroom - Mutune, Fellis Nthambi; Maroko, Geofrey; Kiai, Alice (Machakos University Press, 2021)
An English textbook plays a crucial role in a secondary school level classroom in Kenya. It gives newly recruited tutors proper guidelines in the English course and learning activities. It enhances continuity and consistency in the presentation of content and presents students with a sense of system and progress. Further, textbooks play a crucial role in modelling the required values, social behavior and norm; it provides a lens through which the world is portrayed thus acting as a potential medium of socialization. English is an important language in Kenya and the world at large. Languages textbooks especially the English ones assist learners in attaining communicative competence. English language textbooks play a central role in teaching and learning in many developing countries where English is either a subject and/ or medium of instruction. English is one of the languages offered in the Kenyan secondary school curriculum, and it is the medium of instruction for all the other subjects offered (except for other languages). Textbooks are critical materials used to support the implementation of the curriculum. The textbooks provide input in the form of explanations, texts and activities to simplify educational activities that appear complex. Specifically, the linguistic items and the visual images used in the presentation of the content are key in ensuring production of quality English textbooks. Again, textbooks are agents of effective and long lasting change that shape learners’ mindsets, perceptions, and attitudes in their later life. Textbooks are crucial tools in as far as the conveyance of direct or indirect meanings regarding the way happenings produced in society is concerned. Specifically the language textbooks are influential instruments, which present indelible experiences to the learners. Consequently, it is important to think about this powerful tool in the Kenyan classroom.
Keywords: Textbook; English; Curriculum; Reflection